The Effect of Financial Literacy, Financial Planning and Financial Management on Financial Performance in Transportation Service Companies in Sidoarjo Regency: Pengaruh Literasi Keuangan, Perencanaan Keuangan dan Pengelolaan Keuangan Terhadap Kinerja Keuangan pada Perusahaan Jasa Angkutan di Kabupaten Sidoarjo - Choiron, Ramadhani Nurul; Setiyono, Wisnu Panggah (Indonesian Journal of Innovation Studies, 2022)
Financial performance is important in the company's financial system, because good financial performance will support the company's goals. This research method uses quantitative, this research uses purposive sampling, namely by taking the points needed by researchers with a sample of 20 freight forwarding companies in Sidoarjo with a total of 80 questionnaires. The test results between the variables of financial literacy, financial planning0 and 0 financial management 0 which have the greatest significant value on financial performance are financial literacy, which is 0.003. For 0 variable 0 financial planning of 00.039 and 0 financial management 0 of 00.008. While 0 in the multiple linear regression analysis has a value of 0 constant 0 of 0-3,952. This means that if 0 independent variable = 0.0 then the dependent variable will have a value of -3.952. Where the negative sign here indicates that there is a financial decline.